Simultaneous Measurements of Dinitrogen Fixation and Denitrification Associated With Coral Reef Substrates: Advantages and Limitations of a Combined Acetylene Assay - El-Khaled, Yusuf C.; Roth, Florian; Rädecker, Nils; Kharbatia, Najeh; Jones, Burton H.; Voolstra, Christian R.; Wild, Christian (Frontiers in Marine Science, 2020)
Nitrogen (N) cycling in coral reefs is of key importance for these oligotrophic ecosystems, but knowledge about its pathways is limited. While dinitrogen (N¬2) fixation is comparably well studied, the counteracting denitrification pathway is under-investigated, mainly because of expensive and relatively complex experimental techniques currently available. Here, we combined two established acetylene-based assays to one single setup to determine N2-fixation and denitrification performed by microbes associated with coral reef substrates/organisms simultaneously. Accumulating target gases (ethylene for N2-fixation, nitrous oxide for denitrification) were measured in gaseous headspace samples via gas chromatography. We measured N2-fixation and denitrification rates of two Red Sea coral reef substrates (filamentous turf algae, coral rubble), and demonstrated, for the first time, the co-occurrence of both N-cycling processes in both substrates. N2-fixation rates were up to eight times higher during light compared to dark, whereas denitrification rates during dark incubations were stimulated for turf algae and suppressed for coral rubble compared to light incubations. Our results highlight the importance of both substrates in fixing N, but their role in relieving N is potentially divergent. Absolute N2-fixation rates of the present study correspond with rates reported previously, even though likely underestimated due to an initial lag phase. Denitrification is also presumably underestimated due to incomplete nitrous oxide inhibition and/or substrate limitation. Besides these inherent limitations, we show that a relative comparison of N2-fixation and denitrification activity between functional groups is possible. Thus, our approach facilitates cost-efficient sample processing in studies interested in comparing relative rates of N2-fixation and denitrification.